1997
DOI: 10.1164/ajrccm.155.1.9001327
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural streptokinase versus urokinase in the treatment of complicated parapneumonic effusions: a prospective, double-blind study.

Abstract: Intrapleural administration of fibrinolytics has been shown in small numbers of patients with complicated parapneumonic effusions (CPE) and pleural empyema to be effective and relatively safe. Although streptokinase (SK) is recommended as the fibrinolytic of choice, there are no comparative studies among fibrinolytics. We therefore compared the efficacy, safety, and the cost of treatment two of the most used thrombolytics, SK and urokinase (UK). Fifty consecutive patients with CPE or empyema were randomly allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
122
2
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(135 citation statements)
references
References 0 publications
6
122
2
5
Order By: Relevance
“…Such therapy is intended to lyse the fibrinous septations within infected pleural-fluid collections and is supported by management guidelines. 6,7 Small trials [8][9][10][11][12] and case series 13 have suggested that these agents improve drainage of pleural fluid, as quantified radiographically, and may also reduce the need for surgery, 12 with few adverse effects. These studies have had low statistical power, 14 however, and have therefore been unable to assess accurately whether these benefits translate into a reduction in mortality or in the frequency with which patients require surgical drainage.…”
mentioning
confidence: 99%
“…Such therapy is intended to lyse the fibrinous septations within infected pleural-fluid collections and is supported by management guidelines. 6,7 Small trials [8][9][10][11][12] and case series 13 have suggested that these agents improve drainage of pleural fluid, as quantified radiographically, and may also reduce the need for surgery, 12 with few adverse effects. These studies have had low statistical power, 14 however, and have therefore been unable to assess accurately whether these benefits translate into a reduction in mortality or in the frequency with which patients require surgical drainage.…”
mentioning
confidence: 99%
“…not cause significant activation of systemic fibrinolysis. 15 Allergic reactions have been reported with the use of intrapleural streptokinase with an incidence ranging from 12.5% 16 to less than 5% (R J Davies, personal communication). Urokinase is of human origin and allergic reactions have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are split between one large trial (N = 454) that concludes that thrombolytics should not be used in the treatment of pleural effusion 1 and several smaller studies (N ≤ 100) in favor of the use of thrombolytics in the treatment of pleural effusion [2][3][4][5][6][7][8][9][10] . There are also three meta-analyses of the randomized, placebo-controlled trials written on this topic, all of which conclude that intrapleural thrombolytics likely reduce the need for surgical intervention in some patients, but that the data are heterogenous [11][12][13] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the nine studies that support the use of thrombolytic therapy, five had no control arm; two were retrospective reviews of cases of intrapleural alteplase treatment [2][3] ; two were single-arm prospective studies of similar cases [4][5] ; one was a randomized trial comparing the efficacies of intrapleural streptokinase and intrapleural urokinase, without a control group 6 ; two were single-center, randomized, placebo-controlled trials, using inclusion criteria that were too broad for this situation (patients were grouped together if they had either empyema or a complicated parapneumonic effusion, and only a subset of these patients had loculations) [7][8] ; and the remaining two papers were both double-blind, randomized studies that included patients who had been diagnosed with multiloculated pleural effusions based on ultrasound and/or CT evidence [9][10] . Both of these last studies also required participants to have failed simple tube drainage, which may indicate a blockage of free flow.…”
Section: Literature Reviewmentioning
confidence: 99%